Predictive factors for brachiocephalic and brachiobasilic arteriovenous fistula success : role of colour doppler ultrasound - Gomes, António Pedro da Silva Pinto, 1981- (2018)
Tese de mestrado, Epidemiologia, Universidade de Lisboa, Faculdade de Medicina, 2018